Ameen Rihani and Arab-American literature - Choudhury, Taybur Rahman (International Journal of Psychosocial Rehabilitation, 2020)
Arab-American literature has an important role to play the Arab renaissance in the first half of twentieth century. Ameen Rihani is considered to be the Founding father of Arab-Americanliterature .He inhalesthe first molecule of Oxygen on 24th November of 1876 in Lebanon with a variety of glorious parts of his life tide up by 64 years of life. He was a natural lover, traveller, philosopher, optimist, freedom fighter, patriot and reformer. He tried his utmost to establish a uniform of Arab nations which leads him to a wider thinking of globalization, universal peace and prosperity uprooting the civil atoms of all kinds of diverting hatred. As a Pioneer of revolutionary movement of Arabic literature, Ameen Rihani‘s contributions were mentionable.In the field of wording, composing and prosody of modern Arabic literature, the new reformation of―prose- poetry‖.Perhaps most important of all; he was the first consciously to write Prose- Poetry in Arabic, earning himself the Arabic title of ―Father of Prose Poetry. Ameen Rihani mostly followed the style of Walt Whitman. His literature is full of philosophical thoughts, political advocacy, love of nature and its existence, social reformation. It is notable that every writer or poet aims to bring all round development of the nation mentally, Politically, Socially and culturally. It means that they try to establish the nation a civilized are with all its wings with the help of their literary worlds wring early, simple, rhymical, narrative, sensitive, comprehensive and piercing manner and in this respect, Ameen Rihani could be entitled as the hers of Arab émigrés. As a social reformer he talked for freedom that once mind should be at the out sad free from superstition and blind concepts. He should know what is good and better and what is best for the common people throwing away hatred jealousy or envy. His teaching is to be cleaning mind heart and body, clear and honest opinion that is better for the society. Religion should interpreted in broad a wide manner. The present works ―Ameen Rihani and Arab-American literature ‖ is basically projected on the thinking and contribution of Ameen Rihani and impacted with the. Mahjar Literature.